Growth and development of black soldier fly (Hermetia illucens (L.), Diptera: Stratiomyidae) larvae grown on carbohydrate, protein, and fruit-based waste substrates - Fairuz Liyana Mohd Rasdi,; Ahmad Razali Ishak,; Pui, Wee Hua; Siti Norashikin Mohd Shaifuddin,; Nazri Che Dom,; Farah Ayuni Shafie,; Abdul Mujid Abdullah,; Zulhisyam Abdul Kari,; Hisham Atan Edinur, (Penerbit Universiti Kebangsaan Malaysia, 2022)
There has been a surge in interest in using food waste (FW) as an insect-rearing substrate in recent years. We examine the effect of protein-based food waste (leftover boneless chicken, LBC), carbohydrate-based food waste (overnight rice, OR), and fruit-based food waste (rotten banana, RB) on the following parameters: substrate reduction (SR), waste reduction index (WRI), bioconversion rate (BCR) and relative growth rate (RGR). BSFL reared on OR feed substrate had the highest biomass (0.23±0.01) g at d9 followed by RB (0.22±0.00) g and LBC (0.16±0.00) g. Larvae from OR-fed BSFL were the longest, averaging 20.53±0.46 mm in length on d12. The SR calculated for all feed substrates were as followed: RB (95.35 ± 0.33)% > OR (85.29 ± 0.80)% > LBC (83.17 ± 0.27)%. The WRI for control (C) and BSFL-fed on all feeds were in the following manner: (RBC:8.90±0.00 g days-1, RBBSFL:9.53±0.00 g days-1) > (ORC:7.35±0.00 g days-1, ORBSFL:8.53±0.09 g days-1) > (LBCC:6.90±0.00 g days-1, LBCBSFL: 8.32±0.03 g days-1). OR-fed BSFL showed the highest BCR (76.0±1.0) % and RGR (0.32±0.01) days-1. The FW’s self-composting (as in control) influenced the BSFL’s SR and WRI in all diets. Overall, the BSFL’s growth and development are affected by the nature, quality, and type of diet of the feed substrates.